Transforming coal bottom ash into a high-performance pozzolan: Effects of acid treatment on material properties - Rahimah, Embong (Springer, 2025)
This experimental study explores the transformation of coal bottom ash (CBA), an industrial by-product, into a high-performance pozzolan to replace traditional cement in construction materials. CBA’s disposal has challenges due to its low reactivity and the risk of heavy metal leaching, which limits its sustainable reuse. To overcome these barriers, an innovative acid pre-treatment process was developed, enhancing CBA’s reactivity by removing deleterious materials and increasing silica content. Advanced characterization techniques reveal significantly lower metal content and increased silica content in the treated CBA, demonstrating its potential as a sustainable alternative. Treated CBA shows positively impacts mortar binder properties, as indicated by higher strength activity index values compared to untreated specimens. The treated CBA demonstrated a significant enhancement in mortar binder properties, achieving a 20% higher strength activity index compared to untreated samples. These findings highlight treated CBA’s potential as a sustainable and eco-friendly alternative to conventional cementitious materials. This work advances the utilization of industrial by-products in construction, promoting environmental sustainability and reducing reliance on traditional cement.